EFL Students' Challenges in Pronouncing Inflectional Suffixes: A Case Study of Socotri Students of English - Hamdeen, Sina Bin; Al-Rajdhi, Fatima; Majid, Amna Bin; Al-Jerbhi, Asmaa; Al-Rajdhi, Latifa (Journal of Digital Sociohumanities, 2024)
This study aims to measure the proficiency level of Socotri EFL students in pronunciation of inflectional suffixes, /d/ and /s/. Quantitative data were collected through a test from a group of 24 English language students from the first and second levels at the College of Education, Humanities and Applied Sciences in Socotra. The results of the study showed that the students scored accepted in the pronunciation test with 61.92%. Results also showed that Socotri students suffer from difficulty in pronunciation, especially in the suffix /d/ more than /s/. The study also found differences in students' scoring in the tests in which male students scored (M=23.37) higher than female students (M=20.12) and second level (M=23.72) scored higher than first level (M=21.07), but they were not significant. The study recommends EFL teachers to focus on the practical aspect rather than the theoretical aspect while teaching pronunciation and speaking and listening skills. We also recommend choosing teachers who are fluent in English language teaching.